Awareness and Prevalence of Skin Bleaching Among Female University Students in Garowe City, Somalia - Mohamed, Ahmed Farah; Arbab, Ismail Adam (British Journal of Healthcare and Medical Research, 2025)
Background: Skin bleaching (SB), also referred to as skin lightening (SL), is a growing public health concern affecting individuals across skin tones. Despite its increasing popularity, data on SL practices among university students in Somalia particularly in Garowe City remain limited. This study aimed to assess the prevalence, awareness, attitudes, and associated factors related to the use of skin bleaching products among female university students. Methods: A cross-sectional, questionnaire-based survey was conducted among female students at the University of Bosaso campuses in Garowe City. The survey collected data on sociodemographic characteristics, knowledge, attitudes, commonly used skincare products, and motivations for product use. A market assessment was also carried out to identify the types of skin lightening agents, active ingredients, and pricing of available products. Results: A total of 322 female students completed the survey. The prevalence of self-reported skin bleaching was 95.3%, with 67.1% of users reporting the use of more than two products. The average age of respondents was 23 ± 3.3 years, with the majority (36.3%) aged between 21 and 24. Peer recommendations were the most common influence on SL product use. The primary motivations included enhancing beauty and achieving healthy skin (97.3%), portraying a higher social status (27.7%), and treating skin disorders (24.1%). Most participants obtained products from cosmetic shops (69.8%) and open markets (60.5%). Conclusion: Skin bleaching practices are alarmingly prevalent among female university students in Garowe City, largely influenced by peer networks. These findings highlight the urgent need for health education campaigns focusing on the risks of skin bleaching, clarification of misconceptions, and stricter regulation of harmful cosmetic products.